A YH3 promoted palladium catalyst for reversible hydrogen storage of N-ethylcarbazole. (27th November 2020) - Yang, Xue; Wu, Yiman; Yu, Hongen; Sun, Min; Zheng, Jie; Li, Xingguo; Lin, Wei; Wu, Yong
Abstract: N -ethylcarbazole (NEC) is a promising liquid organic hydrogen carrier, while sluggish kinetics of hydrogen absorption and desorption restrict its application. To overcome that, a YH3 promoted palladium catalyst Pd/Al2 O3 -YH3 is developed in this work by taking advantage of the fast reversible hydrogenation and dehydrogenation kinetics of YH3 . With the Pd/Al2 O3 -YH3, NEC can reversibly store 5.5 wt% hydrogen in 4 h below 473 K. The performance is the best compared to that of all the reported catalysts for both hydrogen absorption and desorption. Moreover, there are no gaseous impurities produced and no performance decay during three hydrogen storage cycles. The excellent performance derives from the intrinsic high catalytic activity of Pd/Al2 O3 and the promoting effect of YH3 by providing a new hydrogen transfer path, making NEC more attractive for practical application. Graphical abstract: Image 1 Highlights: A novel two-direction catalyst Pd/Al2 O3 -YH3 for N -ethylcarbazole is developed. 5.5 wt%-capacity reversible liquid-state hydrogen storage below 473 K is achieved. The performance of Pd/Al2 O3 -YH3 is the best among the existing catalysts. The hydrogen transfer path provided by YH3 plays a key role for the performance.